The Effect of Technology-Based Learning Media: Increasing Student Interest in Learning in the Digital Age - Jannah, Miftahul; Izati, Wilrahmi; Aprilia, Dina; Nurjanah, Siti; Afandi, Septia; Hafizhah, Hafizhah (International Journal of Islamic Teaching and Learning, 2024)
Technology-based media is very important in learning, in line with the demands of the digital and technological era. It can create a creative and effective learning atmosphere, foster growth, and increase student interest in learning. This study aims to analyze the effect of technology-based learning media on student interest in Aqidah Akhlak subjects in Madrasah. This research uses quantitative methods with a descriptive approach. Data were collected from grade X students of Islamic Senior High School. The sampling technique used was total sampling technique, with a sample size of 60 students. The results of data analysis show that the use of technology-based learning media affects student interest in Aqidah Akhlak subjects by 15.2%. These findings can be preliminary data for future researchers to explore the use of technology in learning with different contexts and issues.